Comparative Analysis of The Performance of State-Owned and National Private Companies in The Banking Sub-Sector Using the RGEC Model - Mahdi Mahdi; Ribka Sari Butar-Butar; Henky Hendrawan; Merissa Fermica Iskandar; Imam Hanafi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of this study was to evaluate the profitability and soundness of state, national, and foreign private banks using the one-way ANOVA test and analyze the impact of RGEC ratios on profitability using the panel data regression statistical test using the random effect model. Issuers in the banking sub-sector from 2017 to 2022 make up the study's sample. The simultaneous panel data regression results (prob. F of 0.00) show that RGEC ratios have an influence on profitability as proxied by ROA. Partially, the independent variables NPL, PDN, and GCG have an influence on ROA, while LDR and CAR have no effect on ROA. The results of the one-way ANOVA test show that there are differences in bank profitability and health between state, national, and foreign private banks. Post-hoc analysis shows that state banks have better profitability than national and foreign private banks.